Hubungan Faktor Lingkungan, Kebijakan Pemerintah Dan Pengetahuan Orang Tua Dengan Pencegahan Penyakit TBC Pada Anak - Widiawati, Susi; Puspita, Mefrie; Meinarisa, Meinarisa (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction:Â The prevalence of TB cases was recorded to increase in 2019 in Jambi City reaching 3,423 cases, while the incidence of TB in children was 84 (confirmed).Objectives: Â The purpose of this study was to determine the relationship between environmental factors, government policies, and parental knowledge with the prevention of TB in children in Jambi City. Methods: This research is a quantitative study with a cross-sectional design, the sample is the parents who have children aged 0 years to 18 years in Jambi City with a purposive sampling technique, the number of samples is 82 people. Data collection using online questionnaires, namely environmental factors, government policies, knowledge, and prevention of tuberculosis in children, the data were analyzed univariately and bivariate with the Spearman Correlation test Results: The univariate results of environmental factors met the requirements of 56.1% of respondents, getting information on government policies was 53.7%, moderate knowledge was 43.9%, good TB prevention was 65.9%. The results of the bivariate analysis, there is a relationship and correlation between environmental factors P-value 0.007 and r = 0.296, government policy 0.019 and r = 0.259, and knowledge of p-value 0.043 and r-0.224 with the prevention of TP in children. Conclusions: Â in this study is the prevention of pulmonary TB in children is supported by environmental factors, government policies, and parental knowledge.